Optimization of lubrication techniques on machining performance of aluminium alloy 319 - Zainal Ariffin, Selamat (2018)
Traditionally, the selection of cutting parameters for machining was left to the machine operator. In industries, the machining parameters are dependent on the experience and skill of the machine operator to achieve an optimal product quality. The disadvantage of this unscientific practice is low in productivity due to the sub optimal use of machining capability. The challenges in the modern machining industries are mainly focused on the machining performance on the surface roughness, temperature and tool life with reducing the coolant utilization. The objective of this research is to optimize nozzle lubricant system in machining performance of aluminum alloy 319 (A319) to achieve a good surface roughness, lower temperature and increased tool wear by selecting suitable machining parameters of cutting speed, depth of cut and feed rate. The coolant system used are dry, wet and optimum coolant nozzle size of 1.0 mm, 2.0 mm, 3.0 mm 4.0 mm and 5.0 mm on the surface roughness, temperature and tool life using Respond Surface Method (RSM) on the CNC Lathe machine with 2 axes movements. The surface roughness is measured using Surface Roughness Tester, temperature is measured using Infrared Laser Thermometer and tool wear is measured using Tool Maker’s Microscope. The synthetic soluble oils, coated cemented carbide Al2 O3 insert and Aluminum alloy 319 were used as a cutting tool and workpiece material respectively. The effect of cutting parameters towards surface roughness, temperature and tool wear were analyzed using Analysis of Variance (ANOVA) method and to achieve optimum machining performance by using Respond Surface Method (RSM). Multi-optimization of cutting parameters is used in ensuring product quality and minimizing the energy effects of machining. The results of the nozzle size of 1.0 mm shows a good surface roughness, lower temperature and reduced tool wear compared to 2.0 mm, 3.0 mm, 4.0 mm and 5.0 mm nozzle size. In lubrication techniques experiment, the analysis using ANOVA show that the main factor affecting the surface roughness, temperature and tool wear as machining performance is the used nozzle size of 1.0 mm. Cutting speed of 270 m/min, depth of cut of 0.20 mm, feed rate of 0.08 mm/min and nozzle size lubrication techniques of 1.0 mm are the optimum parameters for improving and achieving the surface roughness of 0.94 μm Ra, temperature of 91C, tool wear length of 0.48 mm and the machining time taken is 120 minutes for tool life. The optimum parameters setting are verified with experimental validation with maximum 4 percent error and obtained optimal desirability value of 0.935 for the respective values of cutting speed, depth of cut, feed rate and coolant nozzle of 1.0 mm. In conclusion, the optimum overall performance in terms of surface roughness, temperature and tool wear with the smallest orifice size coolant and different cutting parameters can be developed using RSM technique. Current research is also beneficial to minimize and improve the productivity in machining industries. Consequently, reducing the dependent on the machining operators experience and skill.